PENGARUH NOPAT DAN GOODWILL TERHADAP NILAI TAMBAH EKONOMIS (EVA) PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (BURSA EFEK INDONESIA) PADA TAHUN 2015-2018 - Dyana Fitriyah; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to analyze NOPAT and goodwill for economic value added (EVA) in manufacturing companies listed on the Indonesia stock exchange in 2015-2018. This research is quantitative research. The sampling method used is purporsive sampling. Obtained from 162 manufacturing companies and a sample of 50 from manufacturing companies. The analysis used is multiple linear regression. Simultaneous NOPAT and goodwill have a significant impact on economic value (EVA). And partially NOPAT on the table coefficient obtained a result of 0.007 so that it is significant towards economic added value (EVA) while the goodwill in the table coefficient obtained a result of 0.417 so that partially it does not have a significant effect on economic value (EVA). Keywords: NOPAT, goodwill, EVA